2x+5y=30
tìm x y
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)5X2 - 2y = 8
2X + y = 5
b) 2X + y = 3
X – 2y = 4
c) 3X + 3y = 1
2X – y = -8
d) 4X + 5y = 3
X – 5y = 5
a) ( 10x3y - 5x2y2 - 25 x4y3) : ( -5xy)
Ta có : -5xy( -2x2 + xy + 5x3y2) : ( - 5xy)
Vậy , ta được thương là : -2x2 + xy + 5x3y2
b) ( 27x3 - y3) : ( 3x - y)
Ta có : ( 3x - y)( 9x2 + 3xy + y2) : ( 3x - y)
Vậy , ta được thương là : 9x2 + 3xy + y2
C,D chịu
\(5x^2+15x=5x^2-30\)
\(5x^2+15x-5x^2=-30\)
\(15x=-30\)
\(x=-2\)
a)
\(\dfrac{x}{5}=\dfrac{y}{2}=\dfrac{3x-2y}{3.5-2.2}=\dfrac{-55}{11}=-5\)
=> \(\left\{{}\begin{matrix}x=-5.5=-25\\y=-5.2=-10\end{matrix}\right.\)
b)
\(\dfrac{x}{3}=\dfrac{y}{2}=\dfrac{2x+5y}{2.3+5.2}=\dfrac{48}{16}=3\)
=> \(\left\{{}\begin{matrix}x=3.3=9\\y=3.2=6\end{matrix}\right.\)
c)
Có: \(\dfrac{x}{y}=-\dfrac{5}{2}\Leftrightarrow-\dfrac{x}{5}=\dfrac{y}{2}=\dfrac{x+y}{-5+2}=\dfrac{30}{-3}=-10\)
=> \(\left\{{}\begin{matrix}x=-10.-5=50\\y=-10.2=-20\end{matrix}\right.\)
d)
Có: \(\dfrac{x}{y}=\dfrac{4}{3}\Leftrightarrow\dfrac{x}{4}=\dfrac{y}{3}=\dfrac{2x+3y}{2.4+3.3}=\dfrac{34}{17}=2\)
=> \(\left\{{}\begin{matrix}x=2.4=8\\y=2.3=6\end{matrix}\right.\)
\(a,4x=5y\:\Rightarrow\frac{x}{5}=\frac{y}{4}\Rightarrow\frac{x}{15}=\frac{y}{12}\)
\(4y=6z\Rightarrow\frac{y}{6}=\frac{z}{4}\Rightarrow\frac{y}{12}=\frac{z}{8}\)
\(\Rightarrow\frac{x}{15}=\frac{y}{12}=\frac{z}{8}\)
\(\Rightarrow\frac{x}{15}=\frac{2y}{24}=\frac{3z}{24}\)
\(\Rightarrow\frac{x-2y+3z}{15-24+24}=\frac{x}{15}=\frac{y}{12}=\frac{z}{8}\)
\(\Rightarrow\frac{5}{15}=\frac{x}{15}=\frac{y}{12}=\frac{z}{8}\)
\(\Rightarrow\frac{1}{3}=\frac{x}{15}=\frac{y}{12}=\frac{z}{8}\)
\(\Rightarrow\hept{\begin{cases}x=\frac{1}{3}\cdot15=5\\y=\frac{1}{3}\cdot12=4\\z=\frac{1}{3}\cdot8=\frac{8}{3}\end{cases}}\)
a)
\(\begin{array}{l}\left( {2x - 5y} \right)\left( {2x + 5y} \right) + {\left( {2x + 5y} \right)^2}\\ = \left( {2x + 5y} \right)\left( {2x - 5y + 2x + 5y} \right)\\ = \left( {2x + 5y} \right).4x\\ = 2x.4x + 5y.4x\\ = 8{x^2} + 20xy\end{array}\)
b)
\(\begin{array}{l}\left( {x + 2y} \right)\left( {{x^2} - 2xy + 4{y^2}} \right) + \left( {2x - y} \right)\left( {4{x^2} + 2xy + {y^2}} \right)\\ = {x^3} + {\left( {2y} \right)^3} + {\left( {2x} \right)^3} - {y^3}\\ = {x^3} + 8{y^3} + 8{x^3} - {y^3}\\ = \left( {{x^3} + 8{x^3}} \right) + \left( {8{y^3} - {y^3}} \right)\\ = 9{x^3} + 7{y^3}\end{array}\)
\(\left\{{}\begin{matrix}2x=5y\\x-y=9\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}2x-5x=0\\x-y=9\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}2x-5y=0\\2x-2y=18\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}3y=18\\2x-2y=18\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}y=6\\x=15\end{matrix}\right.\)